2015
DOI: 10.1177/0308022614562785
|View full text |Cite
|
Sign up to set email alerts
|

‘Drive Safe’ initiatives: An analysis of improvements in mental health practices (2005–2013) to support safe driving

Abstract: Statement of context: Driving can be important for enabling community participation. Mental illness and its treatment may disrupt fitness to drive, or people's opportunities for learning to drive. This paper reflects on practice improvements in an Australian mental health organization. Critical reflection on practice: Occupational therapists identified gaps in knowledge among the multidisciplinary workforce about service users' driver status, how to identify and manage driving issues, and how to support their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Identifying more accurately those who are clearly safe or clearly unsafe to drive on screen allows the specialized resource to be utilized for the very complex assessments. Further, this study echoes the findings of Dun et al (2015a), suggesting that the cost of the specialized driving programs is a limiting factor for the psychiatric population, which requires attention and a need for future advocacy. As legislation evolves, it is expected that driving screening will become an instrumental activity of daily living that will demand attention, such as the Australian ''Drive Safe'' initiatives (Dun et al, 2015a).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Identifying more accurately those who are clearly safe or clearly unsafe to drive on screen allows the specialized resource to be utilized for the very complex assessments. Further, this study echoes the findings of Dun et al (2015a), suggesting that the cost of the specialized driving programs is a limiting factor for the psychiatric population, which requires attention and a need for future advocacy. As legislation evolves, it is expected that driving screening will become an instrumental activity of daily living that will demand attention, such as the Australian ''Drive Safe'' initiatives (Dun et al, 2015a).…”
Section: Discussionsupporting
confidence: 80%
“…However, as Me´nard et al (2006) point out, psychiatrists in particular are often unaware of the legislation in their location of practice and their associated responsibility with reporting driving concerns. Marshall and Gilbert (1999) and Dun et al (2015a) found there was a lack of adequate education and training regarding screening of atrisk drivers for healthcare professionals, including physicians. Again, they indicated the need for guidance with determining which drivers may be at risk and require further assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• Not applicable provided by occupational therapists specialised in mental health practice and with recognised training in driving assessment (Dun, Baker et al, 2015;Dun, Bull et al, 2015). Driving assessment is imbedded in occupational therapy practice.…”
Section: Schizophreniamentioning
confidence: 99%